Digestive-tract sarcoidosis: French nationwide case–control study of 25 cases. Issue 29 (July 2016) - Ghrenassia, Etienne; Mekinian, Arsene; Chapelon-Albric, Catherine; Levy, Pierre; Cosnes, Jacques; Sève, Pascal; Lefèvre, Guillaume; Dhôte, Robin; Launay, David; Prendki, Virginie; Morell-Dubois, Sandrine; Sadoun, Danielle; et al.
Abstract : Abstract: Digestive tract sarcoidosis (DTS) is rare and case-series are lacking. In this retrospective case–control study, we aimed to compare the characteristics, outcome, and treatment of patients with DTS, nondigestive tract sarcoidosis (NDTS), and Crohn disease. We included cases of confirmed sarcoidosis, symptomatic digestive tract involvement, and noncaseating granuloma in any digestive tract. Each case was compared with 2 controls with sarcoidoisis without digestive tract involvement and 4 with Crohn disease. We compared 25 cases of DTS to 50 controls with NDTS and 100 controls with Crohn disease. The major digestive clinical features were abdominal pain (56%), weight loss (52%), nausea/vomiting (48%), diarrhea (32%), and digestive bleeding (28%). On endoscopy of DTS, macroscopic lesions were observed in the esophagus (9%), stomach (78%), duodenum (9%), colon, (25%) and rectum (19%). As compared with NDTS, DTS was associated with weight loss (odds ratio [OR] 5.8; 95% confidence interval [CI] 1.44–23.3) and the absence of thoracic adenopathy (OR 5.0; 95% CI 1.03–25). As compared with Crohn disease, DTS was associated with Afro-Caribbean origin (OR 27; 95% CI 3.6–204) and the absence of ileum or colon macroscopic lesions (OR 62.5; 95% CI 10.3–500). On the last follow-up, patients with DTS showed no need for surgery (versus 31% for patients with Crohn disease; P = 0.0013), and clinical digestive remission was frequent (76% vs. 35% for patients with Crohn disease; P = 0.0002). The differential diagnosis with Crohn disease could be an issue with DTS. Nevertheless, the 2 diseases often have different clinical presentation and outcome.